Proceedings of the 1st ACM/IEEE-CS Joint Conference on Digital Libraries 2001
DOI: 10.1145/379437.379476
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive access to printed materials (CAPM)

Abstract: The CAPM Project features the development and evaluation of an automated, robotic on-demand scanning system for materials at remote locations. To date, we have developed a book retrieval robot and a valuation analysis framework for evaluating CAPM. We intend to augment CAPM by exploring approaches for automated page turning and improved valuation. These extensions will results in a more fully automated CAPM system and a valuation framework that will not only be useful for assessing CAPM specifically, but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…In addition, the findings of this study corroborated the findings of Nakhoda and Tajik (2017) who found that academic librarians at the University of Tehran are aware of the usefulness of AI technologies in libraries. Other studies that affirm this study include Frey and Osborne (2017) and Choudhury et al . (2001).…”
Section: Research Question 3: Are Academic Librarians Aware Of the Po...supporting
confidence: 63%
“…In addition, the findings of this study corroborated the findings of Nakhoda and Tajik (2017) who found that academic librarians at the University of Tehran are aware of the usefulness of AI technologies in libraries. Other studies that affirm this study include Frey and Osborne (2017) and Choudhury et al . (2001).…”
Section: Research Question 3: Are Academic Librarians Aware Of the Po...supporting
confidence: 63%
“…The user can view or print the required page and choose to return or borrow the book. Once the text is scanned, the user can also use CAPM to perform automatic text analysis options [15].…”
Section: B Intelligent Management 1) Intelligent Warehouse Managementmentioning
confidence: 99%
“…As part of JHU's CAPM Project (JHU, n.d.; Choudhury et al, 2001;Suthakorn et al, 2002, Suthakorn and, Choudhury and consultant Nicholas Flores developed an evaluation methodology using multi-attributed, state-preference techniques (Choudhury et al, 2002). Multi-attribute, stated-preference methods feature choice experiments to gather data for modeling user preferences.…”
Section: Capmmentioning
confidence: 99%